2004
DOI: 10.1038/sj.leu.2403434
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation changes in multiple myeloma

Abstract: Using a candidate gene approach, we analyzed the methylation status of the promoter-associated CpG islands of 11 wellcharacterized tumor suppressor genes by methylation-specific polymerase chain reaction in five multiple myeloma (MM) cell lines and 56 patients with malignant plasma cell disorders. The frequency of aberrant methylation among the patient samples was 46.4% for SOCS-1, 35.7% for p16, 21.4% for E-cadherin, 12.5% for DAP kinase and p73, 1.8% for p15, MGMT as well as RARb, and 0% for TIMP-3, RASSF1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 30 publications
4
109
4
Order By: Relevance
“…The difference in our results, compared with this study, may be accounted for the use of nonenriched plasma cells for the methylation-specific PCR technique; hence, Galm et al 35 probably would have underestimated the true frequency of this epigenetic event. Nevertheless, our findings support the work of Kotoula et al, 36 who described low expression or absence of hMLH1 in multiple myeloma samples with extensive bone marrow infiltration using a multiplex RT-PCR technique; they suggested that a deficiency of hMLH1 confers an unfavourable prognosis for multiple myeloma.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The difference in our results, compared with this study, may be accounted for the use of nonenriched plasma cells for the methylation-specific PCR technique; hence, Galm et al 35 probably would have underestimated the true frequency of this epigenetic event. Nevertheless, our findings support the work of Kotoula et al, 36 who described low expression or absence of hMLH1 in multiple myeloma samples with extensive bone marrow infiltration using a multiplex RT-PCR technique; they suggested that a deficiency of hMLH1 confers an unfavourable prognosis for multiple myeloma.…”
Section: Discussioncontrasting
confidence: 93%
“…Hypermethylation of MGMT was observed in seven cases of multiple myeloma (including one case of plasma cell leukaemia) while only one monoclonal gammopathy of undetermined significance sample showed methylation. The frequency of MGMT methylation was higher in our series, compared to other studies: Galm et al 35 (1.8% in multiple myeloma); Seidl et al 37 (7% in myeloma and 4% in monoclonal gammopathy of undetermined significance); Rossi et al 38 (12.5% in multiple myeloma); and Chim et al 39 (0% in multiple myeloma). Once more, this discrepancy may be attributed to the use in those studies of not-purified plasma cells.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although no methylation of P73 gene was detected in all 13 MM patients, 65 another group reported P73 hypermethylation in 40% MM cell lines and in 12.5% MM patients examined (Table 1). 73 Finally, in a larger study on 142 patients with MM or MGUS, P73 methylation was detected in 15 and 21% of them, respectively. 74 Thus, silencing of P73 gene by its methylation is markedly associated also with MG.…”
Section: P73 Gene Hypermethylationmentioning
confidence: 94%
“…DNA methylation is catalysed by DNA methyltransferases (DNMTs), which transfer the methyl moiety from the methyl donor S-adenosyl-methionine to the 5 position on the cytosine ring. Pharmacologic inhibition of DNMT in cancer cells causes reversal of promoter methylation associated with transcriptional activation of methylated tumor suppressor genes including p16, p15 and p73 (Galm et al, 2004). DNMT1 interacts directly with HDAC 1 and 2 as well as the histone methyltransferase SUV39H1 (Vaute et al, 2002).…”
Section: Introductionmentioning
confidence: 99%